Early accretion of water and volatile elements to the inner Solar System: evidence from angrites. (28th May 2017) - Sarafian, Adam R.; Hauri, Erik H.; McCubbin, Francis M.; Lapen, Thomas J.; Berger, Eve L.; Nielsen, Sune G.; Marschall, Horst R.; Gaetani, Glenn A.; Righter, Kevin; Sarafian, Emily
Abstract : Inner Solar System bodies are depleted in volatile elements relative to chondrite meteorites, yet the source(s) and mechanism(s) of volatile-element depletion and/or enrichment are poorly constrained. The timing, mechanisms and quantities of volatile elements present in the early inner Solar System have vast implications for diverse processes, from planetary differentiation to the emergence of life. We report major, trace and volatile-element contents of a glass bead derived from the D'Orbigny angrite, the hydrogen isotopic composition of this glass bead and that of coexisting olivine and silicophosphates, and the 207 Pb– 206 Pb age of the silicophosphates, 4568 ± 20 Ma. We use volatile saturation models to demonstrate that the angrite parent body must have been a major body in the early inner Solar System. We further show via mixing calculations that all inner Solar System bodies accreted volatile elements with carbonaceous chondrite H and N isotope signatures extremely early in Solar System history. Only a small portion (if any) of comets and gaseous nebular H species contributed to the volatile content of the inner Solar System bodies. This article is part of the themed issue 'The origin, history and role of water in the evolution of the inner Solar System'.